2006
DOI: 10.1111/j.1475-4754.2006.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Silvering Process of the Gallo‐roman Coins Forged During the Third Century Ad*

Abstract: We have observed by fast neutron activation analysis (FNAA) that the global composition of the official silver coins of the Gallic emperor Postumus is not the same as those from the contemporary unofficial mints. In order to explain this phenomenon, we have carried out a metallographic study of the artefacts. Then, we have re-created the silvering process of unofficial coins in order to better understand the manufacturing process of silvering. The different steps of the replication process are explained in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
(5 reference statements)
1
7
0
2
Order By: Relevance
“…These results are in a good agreement with the SEM (Figs (c) and 2 (d)) and line scan analysis (see below), which confirmed that the top layer is almost pure silver, which covers a core with a significantly lower amount of silver. Our results are in a good agreement with previous papers dealing with ancient and medieval coins (Linke et al ; Deraisme et al ). The formation of the surface layer could be explained by blanching technology.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in a good agreement with the SEM (Figs (c) and 2 (d)) and line scan analysis (see below), which confirmed that the top layer is almost pure silver, which covers a core with a significantly lower amount of silver. Our results are in a good agreement with previous papers dealing with ancient and medieval coins (Linke et al ; Deraisme et al ). The formation of the surface layer could be explained by blanching technology.…”
Section: Resultssupporting
confidence: 94%
“…The resulting compact silver layer protects the internal part of the coin, with a higher copper content, against corrosion and suggests that the minted coins are made of a much higher‐quality metal. The silvering process was very often abused by the coin issuer, as is already known from ancient Rome (Deraisme et al ). The inhomogeneity of the coin alloy can easily be observed by the optical microscope on a metallographic cross‐section (Figs (a) and 2 (b)), due to the immiscibility of Ag–Cu (NIST ).…”
Section: Resultsmentioning
confidence: 99%
“…н.э.? По-видимому, нет: результаты картирования химических элементов на поверхности статера Савромата IV № 2151 (как и монет Тейрана) демонстрируют отсутствие ртути 46 , что косвенно свидетельствует в пользу использования техники горячей плакировки монет серебряной фольгой (в случае с боспорскими монетами -золотосеребряной), что также доказано экспериментально для римских монет 47 . Метод горячей плакировки известен в римском монетном деле более раннего периода 48 , а также в чеканке Галльской Империи III в. н.э.…”
Section: сравнение с римскими серебряными номиналамиunclassified
“…Метод горячей плакировки известен в римском монетном деле более раннего периода 48 , а также в чеканке Галльской Империи III в. н.э. 49…”
Section: сравнение с римскими серебряными номиналамиunclassified
“…The analytical examination of silver and silver-plated cultural heritage objects is no exception [5][6][7][8]. Most of the past and present scientific studies of these silver or silver-plated objects, deal with on the examination of coins [9][10][11][12][13][14][15][16][17][18][19][20][21][22], or jewelry [23]from ancient and medieval cultures. Although some studies have been performed on more modern silver alloy objects [24][25][26][27][28], there still exist a void for the study and characterization of electroplated silver objects from the Modernist movement of the late 19 th and early 20 th Century.…”
Section: Introductionmentioning
confidence: 99%